Radiologic Assessment of the Sinonasal Tract, Nasopharynx and Mastoid Cavity in Patients with SARS-Cov-2 Infection Presenting with Acute Neurological Symptoms. (November 2021) - Moonis, Gul; Mitchell, Ryan; Szeto, Betsy; Lalwani, Anil K.
Background: Acute neurological sequela in patients with COVID-19 infection include acute thromboembolic infarcts related to cytokine storm and post infectious immune activation resulting in a prothrombotic state. Radiologic imaging studies of the sinonasal tract and mastoid cavity in patients with COVID-19 infection are sparse and limited to case series. In this report, we investigate the radiologic involvement of nasal cavity, nasopharynx, paranasal sinuses, and mastoid cavity in patients with SARS-CoV-2 infection who presented with acute neurological symptoms. Methods: Retrospective review of medical records and neuroradiologic imaging in patients diagnosed with acute COVID-19 infection who presented with acute neurological symptoms to assess radiologic prevalence of sinus and mastoid disease and its correlation to upper respiratory tract symptoms. Results: Of the 55 patients, 23 (42%) had partial sinus opacification, with no evidence for complete sinus opacification. The ethmoid sinus was the most commonly affected (16/55 or 29%). An air fluid level was noted in 6/55 (11%) patients, most commonly in the maxillary sinus. Olfactory recess and mastoid opacification were uncommon. There was no evidence of bony destruction in any of the studies, Cough, nasal congestion, rhinorrhea, and sore throat were not significantly associated with any radiological findings. Conclusion: In patients who present with acute neurological symptoms, COVID-19 infection is characterized by limited and mild mucosal disease within the sinuses, nasopharynx and mastoid cavity. Level of Evidence: 4